How should we use corticosteroids in lateral epicondylitis? Local injection or phonophoresis? (Annals of Medical Research, 2023)
Aim: This study, it was aimed to compare and evaluate the effectiveness of local corticosteroid injection and corticosteroid phonophoresis on grip strength, functional status, pain, and quality of life in lateral epicondylitis.Materials and Methods: Patients with a diagnosis of lateral epicondylitis who underwent corticosteroid phonophoresis or local corticosteroid injection were included in the study. Patients were grouped according to the treatment they received. In the first group, corticosteroid phonophoresis was applied to the lateral epicondyle region using a continuous mode ultrasonic at 1.0 W/cm2 and 1mHz dose with 0.1% betamethasone valerate cream as a conductive agent. In the second group, corticosteroid and local anesthetic injections were applied to the lateral epicondyle region. Two groups received the supervised exercise program. Before treatment and two weeks after treatment, visual analog scale, muscle strength, grip strength, Quick Disabilities of the Arm, Shoulder, and Hand scores, and Nothingom Health Profile results for both groups were recorded from patient files and compared.Results: A total of 43 patients (23 phonophoresis, 20 corticosteroid injections) were enrolled.  Although pain, function, and quality of life of patients improved significantly with both groups, no significant difference was recorded between the groups. Grip and palmar pinch strength significantly increased in only the phonophoresis group. In addition, changing of grip and palmar pinch strength was significantly better in the phonophoresis group than in the corticosteroid injection group.Conclusion: It was determined that corticosteroid administration via phonophoresis instead of injection was more beneficial in terms of grip and palmar pinch strength.
Keywords: Lateral epicondylitis; Phonophoresis; Corticosteroid injection; Corticosteroid therapy